Multiple dimensions of regionally-oriented university involvement: How motivation and opportunity prompt German researchers to engage in different ways - Friedrich Dornbusch; Henning Kroll; Esther Schricke (Fraunhofer Institute for Systems and Innovation Research ISI, 2012)
The present paper aims to draw a comprehensive picture of the ways how university scientists in Germany interact with their regional environment. Previous research documented varieties of localised interactions, however, there have hardly been any broad and systematic approaches explaining the different patterns of regionally-oriented university involvement. This study develops a new typology of researchers' regionally-oriented activities and uses a recent nation-wide survey among German professors to test for main influences on those activities. The results highlight the decisive interplay between an individual academic's motivation as well as different opportunities provided by the regional environment.
urn:nbn:de:0011-n-2236278
Keywords: 330